INTEGRATION OF SUSTAINABLE FOREST MANAGEMENT WITH ECOSYSTEM SERVICES PERFORMANCE IN CLIMATE CHANGE RESILIENCE IN NORTH MOROWALI - Rahman, Abdul; Maiwa, Arman; Hamka, Hamka; Kurniawan, M.; Sofyan, Sofyan (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
Climate change is a major challenge that affects ecosystem resilience and human life, including in Indonesia, especially in North Morowali Regency which has extensive tropical forests. This study aims to assess the contribution of ecosystem services in climate regulation in the region and analyze how climate change interacts with ecosystem performance. The methodology used involves assessing ecosystem services for climate regulation and changes in forest land cover. The study's results indicated that forest dominance significantly aided climate regulation, with conservation forest areas contributing 21.51%, protected forests 20.68%, and production forests 19.52%, particularly in carbon sequestration and climate change mitigation. In contrast, non-forest areas showed a lower contribution. Regional resilience to climate change, it is recommended that the management of conservation and protected forests be strengthened, by considering the potential of ecosystem services they have in mitigating and adapting to climate change.